Accelerometry in Diagnosis of Functional Tremor - Konstantin M. Evdokimov; Ekaterina O. Ivanova; Amayak G. Brutyan; Ekaterina Y. Fedotova; Sergey N. Illarioshkin (Анналы клинической и экспериментальной неврологии)
Introduction. Functional tremor (FT) is the most common phenotype of functional movement disorders. Electrophysiological assessment is included in the diagnostic criteria for tremor; however, there is currently no consensus criteria for the differential diagnosis of FT.